Cisco DCUCI quick reference - Casaletto, James (Cisco Systems, 2010)
"As a final exam preparation tool, the Cisco DCUCI Quick Reference provides a concise review of all objectives on the new DC Unified Computing Implementation Exam (642-983). This eBook provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on performing administrative tasks in UCS, UCS Connectivity, deploying servers, and identifying solutions in UCS. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts"--Resource description page.
Resource description page (viewed Sept. 2, 2010)
Keywords: Computer security; Computer systems; Client/server computing; Computer Security; Computer Systems; Sécurité informatique; Systèmes informatiques; Architecture client-serveur (Informatique); Engineering & Applied Sciences; Computer Science